Hubungan Fenomena Verbal Bullying Dengan Komunikasi Interpersonal di Lingkup Pelajar - Allya Mahira; Nina Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research discusses the relationship between Interpersonal Communication and the phenomenon of verbal bullying among students. It examines the impact of verbal bullying on the students' socialization process. The research is descriptive and employs symbolic interactionist theory. The method used is qualitative, gathering data through interviews with informants. The study concludes that verbal bullying can impact students' interpersonal communication. Interpersonal communication is identified as a key element in preventing bullying cases. Understanding each other better, enhancing empathy, and being mindful of the impact of words in interactions are crucial steps in reducing potentially bullying situations.